2013
DOI: 10.1038/cddis.2013.385
|View full text |Cite
|
Sign up to set email alerts
|

Myotonic dystrophy protein kinase (DMPK) prevents ROS-induced cell death by assembling a hexokinase II-Src complex on the mitochondrial surface

Abstract: The biological functions of myotonic dystrophy protein kinase (DMPK), a serine/threonine kinase whose gene mutations cause myotonic dystrophy type 1 (DM1), remain poorly understood. Several DMPK isoforms exist, and the long ones (DMPK-A/B/C/D) are associated with the mitochondria, where they exert unknown activities. We have studied the isoform A of DMPK, which we have found to be prevalently associated to the outer mitochondrial membrane. The kinase activity of mitochondrial DMPK protects cells from oxidative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 60 publications
0
45
0
Order By: Relevance
“…DMPK-A forms a molecular complex with Src and HK-II at the MOM in skeletal muscle cells subjected to oxidative stress and stabilizes mitoHK-II binding to confer antioxidant protection. 135 (3) Uncoupling proteins (UCPs) are mitochondrial anion carrier proteins that mitigate mitochondrial ROS emission, probably by regulating the mitochondrial membrane potential. 136 A recent study using UCP3 KO mice showed that UCP3 enhanced mitoHK-II binding in skeletal muscle, participating in a UCP3-mediated decrease in ROS emission.…”
Section: Other Modulation Of Mitohk-iimentioning
confidence: 99%
“…DMPK-A forms a molecular complex with Src and HK-II at the MOM in skeletal muscle cells subjected to oxidative stress and stabilizes mitoHK-II binding to confer antioxidant protection. 135 (3) Uncoupling proteins (UCPs) are mitochondrial anion carrier proteins that mitigate mitochondrial ROS emission, probably by regulating the mitochondrial membrane potential. 136 A recent study using UCP3 KO mice showed that UCP3 enhanced mitoHK-II binding in skeletal muscle, participating in a UCP3-mediated decrease in ROS emission.…”
Section: Other Modulation Of Mitohk-iimentioning
confidence: 99%
“…The enhanced glycolytic activity of RH cells was also confirmed by their higher glucose uptake and lactate release and by an increase in the expression of both MCT4 and of the glucose transporter GLUT1, compared to RNT cells (Figure 3B-3C and Supplementary Figure S3A). In addition, the expression of Hexokinase II (HK II), the HK isoform highly induced in a variety of tumor cells [28], where it binds to mitochondria and contributes to cell survival [29, 30, 31], was much higher in RH cells than in RNT hepatocytes (Figure 3C), where HK II associated with mitochondria (Supplementary Figure S3B). In RH cells, glycolysis induction matched inhibition of OXPHOS, as demonstrated by decreased oxygen consumption rate (OCR) both in basal conditions and after maximal stimulation with the proton uncoupler carbonyl cyanide-4-(trifluoromethoxy) phenylhydrazone (FCCP) (Figure 3A, right).…”
Section: Resultsmentioning
confidence: 99%
“…93 Cells were preincubated with 20 nM TMRM and 1.6 mM cyclosporine H (Enzo Life Sciences, ALX-380-286), to inhibit the nonspecific cell extrusion of the probe by P-glycoprotein, for 30 min. Cells were washed with PBS, trypsinized, centrifuged and resuspended in 300 ml of PBS.…”
Section: Flow Cytometry Analysismentioning
confidence: 99%